2022
DOI: 10.1093/neuonc/noac251
|View full text |Cite
|
Sign up to set email alerts
|

Changes in outcomes and factors associated with survival in melanoma patients with brain metastases

Abstract: BACKGROUD Treatment options for patients with melanoma brain metastasis (MBM) have changed significantly in the last decade. Few studies have evaluated changes in outcomes and factors associated with survival in MBM patients over time. The aim of this study is to evaluate changes in clinical features and overall survival (OS) for MBM patients. METHODS Patients diagnosed with MBMs from 1/1/2009-12/31/2013 (Prior Era; PE) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…According to previous studies, owing to recent improvements in chemotherapy and radiotherapy, the OS of patients with MBM has increased from approximately 4–14 months 2,10 . However, our study revealed that the outcomes of patients with MBMs in Japan did not improve as significantly as reported in other studies.…”
Section: Discussioncontrasting
confidence: 53%
“…According to previous studies, owing to recent improvements in chemotherapy and radiotherapy, the OS of patients with MBM has increased from approximately 4–14 months 2,10 . However, our study revealed that the outcomes of patients with MBMs in Japan did not improve as significantly as reported in other studies.…”
Section: Discussioncontrasting
confidence: 53%
“…Clinically, corticosteroid exposure prior to initiation of ICI is strongly associated with worse outcomes 62–65 . In a study comparing the outcomes of patients with MBM in the pre‐immunotherapy era and the current immunotherapy era, the presence of symptoms in the pre‐immunotherapy era was not associated with a worse outcome 10 ; probably because almost all MBM patients fared poorly prior to the widespread use of ICI. Taken together, these data suggest that the inferior clinical outcomes of patients with symptomatic MBM may at least be partly due to corticosteroid use.…”
Section: Major Open Questions: Future Researchmentioning
confidence: 99%
“…Combination ICI (ipilimumab and nivolumab) is standard of care for patients with MBM 8,9 . Despite substantially improved clinical outcomes for patients with asymptomatic MBM (response rates of 50%–60%, with median overall survival >5 years), patients with symptomatic MBM respond poorly to treatment with combination ICI (response rates of 15%–20%, with median overall survival <9 months) 7–10 . Patients with symptomatic MBM therefore represent a significant unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…With the differences in clinical prognosis between melanoma patients with LMD and those with parenchymal brain metastases (Hasanov et al, 2022; Raizer et al, 2008), it was clear early on that there was something very unique about the LMD tumors and their microenvironment. Single‐cell RNA sequencing (scRNAseq) approaches have recently been utilized to elucidate and compare the immune landscapes of leptomeningeal metastasis, parenchymal brain metastases, and extra‐cranial metastases.…”
Section: The Biology Of Melanoma Lmdmentioning
confidence: 99%